Conceptual new model of city/town design based on the traditional urban form - Sulaiman, Ahmad Bashri; Shamsuddin, Shuhana; Norbienna, Sharifah Lily; Anwar, Markarius (UTM, 2005)
This research seeks to identify and findings the conceptual new model of city or town design based on the traditional urban form. There were two towns that been used as a case study which is Malacca and Georgetown. The character of the town will be used as a model for the new urban form. The analysis will be focus on urban structure, pattern and townscape, also including the activities and behaviour pattern. The research involves a literature study, questionaire survey, interview and visual survey through extensive field work in the towns. The data obtained were analysed and concluded as a guideline for the model of town. Therefore, the research is to build a model of town based on the tradisional urban form in Malaysia and as an alternative for structured a new town in the future.